Improving Students’ Ability in Writing Narrative Texts by Implementing Picture Series - Fifin Naili Rizkiyah (Linguistic, English Education and Art (LEEA) Journal, 2018)
This study was aimed at finding out whether the implementation of picture series strategy can improve the ability of the students in writing narrative text. The research design was collaborative action research which consisted of two cycles, in where cycle 1 consisted of three meetings and cycle 2 consisted of four meetings. A cycle consisted of four steps namely: planning the action, acting on the plan, observing the action and reflecting on the observation. The subject of the study was the 34 students. The instruments used to collect data were observation checklist, field notes, questionnaires, scoring rubrics and the students’ writings. The data from the observation, scoring rubrics and questionnaires were analyzed and the results are presented in the form of tables and description, while the data gained from the field notes and the students’ writings were analyzed and reported descriptively. The result of the study showed that the picture series effectively improved the students’ ability in writing narrative texts. All students had reached the minimum score of 3. Moreover, the majority of the students gave positive responses towards the implementation of picture series, in the case that 70% of the students showed excitement. Furthermore, they found that picture series is interesting, easy to understand, moreover, it helped them to organize paragraphs and develop ideas in writing narrative texts. Keywords: picture series, writing ability, narrative text.